The frequency and reason for amputations in electrically burned pediatric patients - Tapking, Christian; Hundeshagen, Gabriel; Popp, Daniel; Lee, Jong O.; Herndon, David N.; Zapata-Sirvent, Ramón; Branski, Ludwik Krzysztof (Journal of burn care & research, 2019)
Abstract. Electrical injuries induce substantial morbidity and mortality. Amputations are often necessary to enable survival and based on tissue nonviability,
Published: 27 October 2018
Gesehen am 12.07.2019